Practices of Locating Health Information in an Electronic Environment: Reflections on Conducted Health Information Skills Training. Issue 4 (1st October 2016) - Haruna, Hussein; Wema, Evans
ABSTRACT: Health information skills in an electronic environment are essential to health science librarians, who serve as educators both within and outside of their health training institutions. This reflective study was conducted to examine the application of online health information skills obtained from the training provided for librarians who are working in health settings. Health sciences librarians, as future information skills educators, therefore need to possess their own health information skill sets. Capacity building is vital in order to promote the development of health information skills for health sciences librarians who can then teach and advocate the concept of health information skills on the Internet within and outside of their places of work.